COVID-19 and Liver Surgery: How the Pandemic Affected an Italian Medium-Volume HBP Center - Carissimi, Francesca; Scotti, Mauro Alessandro; Ciulli, Cristina; Fogliati, Alessandro; Uggeri, Fabio; Chiarelli, Marco; Braga, Marco; Romano, Fabrizio; Garancini, Mattia (Frontiers in Surgery, 2022)
Introduction: while the COVID-19 pandemic is still ongoing, it is even more evident that victims of the pandemic are not only those who contract the virus, but also the countless patients suffering from other serious diseases (i.e., tumor) who have undergone delayed potentially life-saving surgery due to lack of beds. Like many hospitals, also ours initially blocked all elective oncologic surgery, but these operations were "recovered" and reintegrated in a relatively short time thanks to the establishment of covid-free wards and operating rooms with staff dedicated to oncological surgery. Our aim is to assess whether and how the SARS-Cov2 pandemic has impacted our hepatobiliary surgery unit. Methods: From our prospective database, we retrospectively took data from patients undergoing liver surgery in 2018-2019 (pre-COVID) and 2020-2021 (COVID period). Patients admitted to covid-free wards must necessarily have a negative nasal swab from the previous 24 hours. Results: Between January 1, 2018, and December 31, 2019 (Group 1), 101 patients were treated; during the pandemic (1 January 2020 and 31 December 2021 - Group 2) 126 patients were treated. There is no statistical difference between the groups. The median postoperative hospital stay was 7 days for both groups; 7 patients had major complications (Clavien-Dindo> 3) in Group 1 and 11 in Group 2 (p = 0.795). 4 patients died in group 1, 6 during the pandemic (P = 0.754). Tumor burden is significantly greater in group 2 where nodule size, lymphadenectomy and extrahepatic disease are significantly greater (P = 0.011, P = 0.004, P = 0.026 respectively). Conclusion: During the COVID pandemic, our HPB unit managed to offer a volume of tertiary-center hepatobiliary surgery without a significant impact in terms of length of stay, morbidity or mortality; despite the increase in tumor burden during the pandemic years.